Cultivating Black liberatory spaces in science, technology, engineering, and mathematics education: What does it take? - Mathews, Channing J.; Robinson, Darrius; Wilkes, Charles E. (Frontiers in Education, 2022)
Black youth who reject this belief carry a heavy burden to resist anti-Black attitudes and continue to strive for excellence. As a result of this antagonistic relationship, many Black learners are led to believe that high competence in the areas of science, technology, engineering, and mathematics (STEM) are beyond their grasp. Such beliefs can lead Black learners to determine that the pursuit of success in STEM is not worthwhile. In our vision for Black Liberatory STEM Spaces, the antagonistic relationship between Blackness and success in STEM is dismantled and the forms of violence that support this association are non-existent. The purpose of this paper is to highlight concrete educational practices that move us toward pedagogy that centers Black joy, creativity, imagination, and liberation within STEM education.